Optimizing wireless power transfer efficiency: an empirical analysis of switching frequency variations - Baharom, Rahimi; Hayat, Muhammad Amirul Ashraf Zarrul (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This study explores the impact of switching frequency variations on wireless power transfer (WPT) system efficiency through rigorous experimental analysis. Our tests reveal that lower switching frequencies can enhance system efficiency by up to 30% by reducing resistive losses. These findings establish an optimal frequency range that significantly improves performance. The research integrates empirical data with theoretical models to elucidate electromagnetic principles like the skin effect and its impact on frequency-dependent behaviors. This comprehensive approach not only confirms the experimental methodology but also provides robust numerical evidence, making a novel contribution to the field. The results have significant implications for renewable energy and sustainable technology development, suggesting practical applications in designing energy efficient WPT systems for consumer electronics and electric vehicle charging. This paper quantitatively defines the efficiency benefits of specific frequency ranges, advancing the deployment of wireless power technologies.